Case Report: Rapidly progressive bilateral pleural effusions in a 12-year-old girl with multisystem inflammatory syndrome who was successfully treated with prednisolone and cyclosporine - Yamamoto, Takeshi; Okunushi, Kentaro; Watanabe, Kei; Hirata, Yutaka; Sato, Hironori; Nagasawa, Koo; Nakano, Taiji; Takatani, Tomozumi; Hamada, Hiromichi (Frontiers in Pediatrics, 2025)
This case report explores a unique presentation of macrophage activating syndrome (MAS) as well as multisystem inflammatory syndrome in children (MIS-C), a complication of COVID-19, that was characterized by polyserositis with massive pleural effusions and edema. A 12-year-old girl had cervical pyogenic lymphadenitis, dyspnea, and cough in addition to the bilateral conjunctivitis, facial edema, erythema on both cheeks, and edema in the extremities. Initial laboratory investigations revealed a white blood cell count of 5.8 × 109/L, hemoglobin 9.7 g/dl, platelet count 75 × 109/L, C-reactive protein level 149 mg/L, serum aspartate aminotransferase 73 U/L, alanine aminotransferase 64 U/L, fibrinogen 446 mg/dl. The dyspnea and cough rapidly worsened and a chest x-ray demonstrated massive plural effusions bilaterally. An echocardiographic study showed slight pericardial effusion and a normal cardiac ejection fraction. Her condition, fever, high serum triglyceride, high serum ferritin level, hemophagocytosis, low NK cell activity, and high serum soluble IL-2R level were attributed to MAS. We started intravenous administration of prednisolone (2 mg/kg). The respiratory distress and pleural effusions showed little change 2 days after starting prednisolone, so we added oral cyclosporine (5 mg/kg/day) based on the HLH-2004 protocol. Soon after starting cyclosporine, the respiratory distress and oxygenation improved and the pleural effusions significantly decreased. One month before admission, the patient's mother had fever and respiratory distress due to PCR-confirmed SARS-CoV-2 infection during the omicron variant wave in Japan. At that time, the patient also had fever. SARS-CoV-2 titers were subsequently tested, revealing that both anti-N antibodies and anti-S protein antibodies were positive. In 2021, there are few patients with COVID-19 in Japan, so the antibody titers were an important diagnostic tool in this period. Taking together these findings, we diagnosed her condition as MIS-C. The case highlights the complex overlap between MIS-C and MAS, with immunosuppressive therapy, particularly cyclosporine, playing a critical role in the management of severe cases.